2001
DOI: 10.1161/01.hyp.37.2.371
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Inhibition of Brain Renin-Angiotensin System Decreased Blood Pressure in Chronic 2-Kidney, 1 Clip Hypertensive Rats

Abstract: Abstract-The systemic renin-angiotensin system (RAS) plays an important role in blood pressure (BP) regulation during the development of 2-kidney, 1 clip (2K1C) hypertension. Its contributions decrease with time after constriction of the renal artery. During the chronic phase, the peripheral RAS returns to normal, but the hypertension is sustained for months. We hypothesized that in this phase the brain RAS contributes to the maintenance of high BP. To test the hypothesis, we studied the role of brain RAS by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 45 publications
2
39
0
1
Order By: Relevance
“…18 Similar results were obtained for other experimental model, namely, 2-kidney-1-clip. 27 Our findings agree with those of Pachori et al, 19 who found moderate antihypertensive effects of AS therapy in young TGR that were accompanied by attenuated cardiac hypertrophy. Our data also demonstrated positive effects of AS therapy on cardiac hypertrophy, as indicated by the decrease in the relative heart weight.…”
Section: Antisensesupporting
confidence: 93%
“…18 Similar results were obtained for other experimental model, namely, 2-kidney-1-clip. 27 Our findings agree with those of Pachori et al, 19 who found moderate antihypertensive effects of AS therapy in young TGR that were accompanied by attenuated cardiac hypertrophy. Our data also demonstrated positive effects of AS therapy on cardiac hypertrophy, as indicated by the decrease in the relative heart weight.…”
Section: Antisensesupporting
confidence: 93%
“…There is considerable evidence that ANG II in the brain plays an important role in maintaining a high level of sympathetic activity in a number of models of experimental hypertension (20,24,44,45). In particular, as mentioned above, very recent studies indicate that, at least in SHR and in the Dahl salt-sensitive hypertensive rat, endogenous ANG II has a tonic excitatory action on presympathetic neurons in the RVLM that is not evident in normotensive animals (1,21,22).…”
Section: Perspectivesmentioning
confidence: 98%
“…This has been tested centrally with intracerebroventricular and intravenous injections. It has been tested in SHR 37 and also in 2-kidney, 1-clip (2K1C) animals 26 and environmentally induced hypertension. 27 In these 3 different models of hypertension-genetic, surgical, and environmental-the antisense produces a decrease in blood pressure within 24 hours of administration.…”
Section: At 1 R As-odnmentioning
confidence: 99%